Implementation of the School Literacy Program as an Effort to Increase the Reading Interest of Students of SDN Harjasari 01 - Utari, Uli Sri; Iin Purnamasari; Sunan Baedowi (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
This research aims to find out 1) What are the supporting factors in implementing the School Literacy Program at SDN Harjasari 01 2) What are the inhibiting factors in implementing the School Literacy Program at SDN Harjasari 01 3) What is the process of implementing the School Literacy Program in increasing interest in reading at SDN Harjasari 01. This type of research uses descriptive qualitative research by processing and collecting data according to facts in the field. Data was obtained from interviews, observation and documentation. The data obtained was analyzed and presented in descriptive form. The subjects of this research were students at SDN Harjasari 01. The results of the research showed that the implementation of the School Literacy Movement at SDN Harjasari 01 had gone well, it was known from the results of interviews with the principal, students, class teachers and observation results as well as from the School Report Card in the Literacy aspect showing scores 60% with moderate indications. Implementation of the School Literacy Movement Program includes reading 15 minutes before learning, providing a library, wall magazine and reading corner. Factors inhibiting the implementation of the School Literacy Movement are lack of interest in reading, limited reading materials, limited and inadequate library space.